PENGARUH PENGGUNAAN AMPAS TAHU YANG DIFERMENTASI DENGAN SACCHAROMYCES SP. PADA RANSUM TERHADAP JUMLAH LEMAK ABDOMEN DAN KADAR KOLESTEROL AYAM BROILER - I P., Januarta; Bidura, I G. N. G.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika; Vol 4 No 2 (2016), 2016)
This research has purpose to find out the influence of tofu dregs using that is fermented by Saccharomyces sp. as probiotic source in rations and broiler chicken’s cholesterol level. Research result shows that supplementation of probiotic Saccharomyces sp. in rations significantly can lower broiler chicken’s fattening, it is because the presence of leavened Saccharomyces sp. in rations as inokulan fermentation that can be functioned as probiotic. Design used in this research is the complete random design (CRD) with 3 treatments and 6 times of repetition; the three treatments are: the chicken supplied with rations without tofu dregs that is fermented by leavened Saccharomyces sp. control (A) chicken supplied with additional rations of 5% tofu dregs fermented by leavened Saccharomyces sp. (B) and chicken supplied with rations of 10% tofu dregs fermented by leavened Saccharomyces sp. (C). Variables that are observed are the mensentrium fat, pad-fat, ventrikulus fat, abdominal fat, blood cholesterol. Research result shows that the using of tofu dregs fermented by leavened Saccharomyces sp. culture in rations at level 5%-10% can lower abdominal fat and broiler chicken’s blood cholesterol level.
Keywords: Probiotic, Saccharomyces sp, Abdomen Fat, and broiler chicken’s blood cholesterol level